Does the diagnosis of multiple myeloma show a seasonal difference? (Annals of Medical Research, 2025)
Aim: Multiple myeloma (MM) is a heterogeneous disease caused by genetic and environmental factors. The present study aims to determine whether the diagnosis of MM exhibits a seasonal pattern.Materials and Methods: Eighty new diagnosed patients with MM between January 2020 and July 2024 were included in the study. All data on gender, age and time of diagnosis were retrospectively analyzed from the files of patients.Results: Eighty patients newly diagnosed with MM were included in the study.  Thirty-four (42.5%) of them were female and 46 (57.5%) were male. The median age of the patients was 63 years (41-81). The month with the highest number of MM diagnoses was November, with nine patients (11.3%), while the month with the least number of diagnoses was July, with four patients (5%).  The season with the highest number of diagnoses was winter, with 22 patients (27.5%) diagnosed, followed by spring and autumn, each with 20 patients (25%).  The least number of MM diagnoses was observed in the summer, with 18 patients (22.5%).  This observation did not reach statistical significance (p>0.05). Among the 80 patients, 44 were diagnosed between October and March, while 36 were diagnosed between April and September. The number of new cases was higher in the colder seasons.Conclusion: In our study, the diagnosis of MM does not appear to show seasonal variation. We observed that new cases with MM increased in the cold months. Since infections are a common presenting feature in Multiple Myeloma (MM), clinicians should maintain a high index of suspicion for MM in patients with recurrent or unusual infections.
Keywords: Multiple myeloma; Seasonal change; Single center; Diagnosis